ERRORS ANALYSIS OF STUDENTS’ DESCRIPTIVE TEXT IN USING SIMPLE PRESENT TENSE AT TENTH GRADE OF SMAN 2 SAMPANG - Khoirul Anam; Moh. Darrin Zuhri (Universitas Madura, 2020)
Language is used in daily of life for making interaction with another people in form of sound and symbol, in order that they can express their ideas, thought, feeling, opinion, and intention to other. There are two problem, first what kinds of errors faced by the students of SMAN 2 Sampang in using simple present tense in descriptive text? And the second what are the causes errors made by the students of SMAN 2 Sampang in using simple present tense in descriptive text?. First to describe the kinds of errors faced by the students of SMAN 2 Sampang in using simple present tense in descriptive text. to identify the causes of errors faced by the students of SMAN 2 Sampang in using simple present tense in descriptive text. this research the researcher was designed by using qualitative research method because the researcher only analyzed data collection without any statistic procedure. The data will be gathered from interview and document. the analyzing of the data conduct gather the information that the research obtains form various sources, observation, interview, document analysis. the result above, this study is suggested for the teacher should give more motivation and support to the students to learn English hardly, so the students can be interested and spirit in grammar genre. And for the students should give more attention to the teacher explanation, so they really understand what the teacher explanation.